The Chinese Dilemma and Research on Internet Child Pornography Crime - Du, Cunlan (Transactions on Social Science, Education and Humanities Research, 2024)
With the development of the Internet Plus initiatives in all industries and sectors, internet child pornography crime has become a serious social issue. This article conducts research on the harm and impact of internet child pornography crime, as well as the inadequacies of legal measures. This study aims to provide theoretical support for combating internet child pornography crimes in China by analyzing the issues faced by China in combating this type of crime, and proposing legal suggestions for improving the regulation of criminal laws in China. Future research could focus on the causes of internet child pornography crime, international cooperation and experiences, and enhancing the strength of social education and public opinion guidance, providing theoretical support and practical guidance for the governance of internet child pornography crime.